Bio-based water-based pressure-sensitive adhesive with high biochar content and preparation method thereof

By adopting the preparation method of high-biocarbon content bio-based water-based pressure-sensitive adhesive in the production of pressure-sensitive adhesives, and using the aqueous reaction system to replace organic solvents, the problems of environmental pollution and resource waste of traditional pressure-sensitive adhesives are solved, and environmental protection and high-attachment are achieved Focus on and sustainable development goals.

CN119242230AActive Publication Date: 2025-01-03UNIV OF SCI & TECH OF CHINA
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411367852.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

The production process of existing pressure-sensitive adhesives requires a large amount of organic solvents, resulting in environmental pollution and waste of resources. Traditional petroleum-based solvent-based pressure-sensitive adhesives are not conducive to sustainable development.

Method used

The preparation method of high biocarbon content bio-based water-based pressure-sensitive adhesive is adopted, using deionized water, emulsifiers, soft monomers, hard monomers, functional monomers, persulfate initiators and aziridine crosslinkers. The aqueous pressure-sensitive adhesive without organic solvents is prepared by emulsification and polymerization, which has good adhesion and is not easy to leave residual glue.

Benefits of technology

The preparation of high-biocarbon content water-based pressure-sensitive adhesives without the use of organic solvents is achieved, which reduces environmental pollution and resource waste, meets the needs of sustainable development, and improves the environmental protection and performance of the adhesives.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242230A_ABST
    Figure CN119242230A_ABST
Patent Text Reader

Abstract

The invention provides a bio-based water-based pressure-sensitive adhesive with high biochar content and a preparation method thereof. The bio-based water-based pressure-sensitive adhesive with the high biochar content is prepared from the following raw materials in parts by weight: 1-10 parts of a curing agent and 1-10 parts of a curing agent, comprising the following raw materials: 280 to 380 parts of deionized water, 1 to 3 parts of sodium bicarbonate, 25 to 35 parts of an alkyl sulfate anionic surfactant A and a polyoxyethylene ether nonionic surfactant B, 180 to 280 parts of a soft monomer S1, 200 to 300 parts of a hard monomer S2, 5 to 12 parts of a functional monomer, 5 to 12 parts of a persulfate initiator and 5 to 12 parts of an aziridine cross-linking agent. Compared with a traditional petroleum-based pressure-sensitive adhesive and a solvent type pressure-sensitive adhesive, the pressure-sensitive adhesive is more environmentally friendly, no organic solvent is needed, potential safety hazards are reduced, and the requirement for sustainable development is better met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of pressure-sensitive adhesives, in particular to a bio-based water-based pressure-sensitive adhesive with a high biocarbon content and a preparation method thereof. Background Art

[0002] The raw materials of most commercial pressure-sensitive adhesives come from petroleum or fossil resources. However, with the increasing demand for sustainable development, bio-based pressure-sensitive adhesives that use natural renewable resources as raw materials have gradually attracted the attention of researchers in the industry.

[0003] Solvent-based pressure-sensitive adhesives require a large amount of organic solvents, such as ethyl acetate, during production, which can cause serious environmental pollution and waste of resources. Environmentally friendly water-based adhesives that replace organic solvents with water have become a major development trend in the adhesive field.

[0004] In the prior art, pressure-sensitive adhesives are usually prepared using vegetable oils such as epoxidized soybean oil or palm oil as renewable resource raw materials, such as the bio-based pressure-sensitive adhesive preparation method disclosed in CN114958300A. However, a large amount of organic solvents are still required to prepare the pressure-sensitive adhesive, which is not conducive to sustainable development. Summary of the invention

[0005] Commercially available pressure-sensitive adhesives are mainly petroleum-based solvent-based pressure-sensitive adhesives, which are not conducive to sustainable development. The purpose of the present invention is to provide a high-biocarbon content bio-based water-based pressure-sensitive adhesive and a preparation method thereof in order to solve the above problems. The water-based pressure-sensitive adhesive provided by the present invention has a high biocarbon content, and no organic solvent is required in the preparation process. The final product has good adhesion to different substrates, and it is not easy to leave residual adhesive after tearing off.

[0006] The present invention adopts the following technical solutions: A method for preparing a bio-based water-based pressure-sensitive adhesive with high biocarbon content: The preparation raw materials mainly include the following by weight: 280-380 parts of deionized water, 1-3 parts of sodium bicarbonate, 25-35 parts of emulsifier, 180-280 parts of soft monomer S1, 200-300 parts of hard monomer S2, 5-12 parts of functional monomer, 5-12 parts of persulfate initiator and 5-12 parts of aziridine crosslinking agent.

[0007] The soft monomer S1 is at least one of n-butyl acrylate and 2-ethylhexyl acrylate.

[0008] Preferably, the hard monomer S2 is derived from an unsaturated acid F containing four carbon atoms. The unsaturated acid F can be produced by fermentation of wood fiber bundles, which can undergo an esterification reaction with biobutanol under the catalysis of concentrated sulfuric acid to obtain the hard monomer S2. For example, the hard monomer S2 is dibutyl fumarate; The functional monomer is at least one of acrylic acid and 4-hydroxybutyl acrylate; the emulsifier is an alkyl sulfate anionic surfactant A and a polyoxyethylene ether nonionic surfactant B; and the aziridine crosslinking agent is trimethylolpropane-tris[3-(2-methylaziridinyl) propionate].

[0009] The alkyl sulfate anionic surfactant A is sodium dodecyl sulfate; the polyoxyethylene ether nonionic surfactant B is OP-10; and the persulfate initiator is potassium persulfate.

[0010] Furthermore, the method comprises the following steps: (a) Prepare monomer pre-emulsion: weigh deionized water and emulsifier, add them into an emulsifying kettle and stir at high speed, then slowly (at a rate of 4-6 ml / min) add soft and hard monomers and functional monomers, stir evenly to prepare monomer pre-emulsion. Preferably, in the monomer pre-emulsion, the mass fraction ratio of soft monomer to hard monomer is in the range of 1:1-1.7 (for example, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4 or 1:1.7); Preferably, in the monomer pre-emulsion, the mass proportion of the functional monomer is in the range of 2-4 wt% (e.g., 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt% or 4 wt%) of the total mass of the three monomers; Preferably, in the monomer pre-emulsion, the mass proportion of deionized water is 20-40 wt % (eg, 20 wt %, 25 wt %, 30 wt %, 35 wt % or 40 wt %).

[0011] (b) Weigh deionized water and emulsifier, add them into a reactor, stir and heat to 70-85°C, take 3-6wt% of the total monomer pre-emulsion liquid and add it into the reactor, add part of the initiator and deionized water (at a rate of 0.7-1.1 ml / min), and polymerize for 25-35 minutes.

[0012] Preferably, the mass ratio of deionized water and emulsifier added to the reactor is in the range of 28-45:1 (e.g., 28:1, 30:1, 35:1, 40:1 or 45:1); Preferably, the initiator added to the reactor is 30% to 70% (e.g., 30%, 35wt%, 40wt%, 50wt%, 60wt% or 70wt%) of the total mass of the initiator; Preferably, the mass ratio of the initiator to the emulsifier is 0.2 to 0.8:1 (e.g., 0.2:1, 0.3:1, 0.5:1, 0.7:1 or 0.8:1); (c) The remaining monomer pre-emulsion (at a rate of 0.7-1.1 ml / min) and the initiator solution (at a rate of 0.05-0.08 ml / min) are slowly added dropwise to the reactor over 3-4 hours.

[0013] (d) After the reaction is completed, the pH value and viscosity are adjusted, and then an aziridine crosslinking agent is added to the emulsion, which is then coated and dried to form a water-based pressure-sensitive adhesive.

[0014] As a preferred technical solution of the present invention, in the monomer pre-emulsion, the mass proportion of deionized water is 20-35 wt %, more preferably 23-27 wt %.

[0015] During the monomer pre-emulsification process, the stirring speed is preferably 200-1000 rpm, more preferably 500-1000 rpm.

[0016] In the monomer pre-emulsion, the monomers should be added slowly in order from weak to strong polarity.

[0017] In the monomer pre-emulsion, the total amount of the two emulsifiers is preferably 2.5-5 wt % of the monomer, and more preferably 4.5-4.8 wt %.

[0018] During the monomer pre-emulsification process, the preferred emulsification temperature is 25-50°C, more preferably 35-50°C.

[0019] During the monomer pre-emulsification process, the preferred emulsification time is 30 min-120 min, more preferably 60-90 min.

[0020] The deionized water added to the reactor is preferably 25-40 wt % of the monomer, more preferably 30-35 wt %.

[0021] The total amount of the two emulsifiers added to the reactor is preferably 1-1.5 wt % of the monomers, more preferably 1.1-1.3 wt %.

[0022] The ratio of the two emulsifiers is preferably anionic surfactant: nonionic surfactant 1:3, more preferably anionic surfactant: nonionic surfactant 1:2.

[0023] In the step (b), the mass fraction of the monomer pre-emulsion added first is preferably 3-10 wt %, more preferably 3-5 wt %.

[0024] In the step (b), the temperature required for the reaction depends on the type of thermal initiator.

[0025] In the step (b), the reaction time is preferably 15-35 minutes, and the emulsion is ensured to be blue.

[0026] In the step (b), the particle size of the obtained polymer emulsion is preferably 50-200 nanometers, more preferably 50-100 nanometers.

[0027] In the step (b), the added initiator is preferably 30-45 wt% of the total initiator amount, more preferably 30-35 wt% of the total initiator amount.

[0028] The pressure-sensitive adhesive latex needs to go through the following steps to be made into a pressure-sensitive adhesive tape: (1) Use ammonia water to adjust the pH value to about 7 before leaving the kettle.

[0029] (2) Remove a small amount of gel by filtration.

[0030] (3) Add small molecule cross-linking agent and stir thoroughly.

[0031] (4) Apply on release film or substrate, dry excess water in a blast oven and cover with release film for protection.

[0032] Advantages and positive effects: Compared with traditional petroleum-based pressure-sensitive adhesives and solvent-based pressure-sensitive adhesives, the bio-based water-based pressure-sensitive adhesive of the present invention is greener and more environmentally friendly, does not require the use of organic solvents, reduces safety hazards, and is more in line with the needs of sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 Schematic diagram of the synthesis route; Figure 2 Infrared image of emulsion demulsification and precipitation of Example 1; Figure 3. Particle size distribution of emulsion. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other. In order to achieve the above-mentioned purpose, the present invention adopts the following technical solution: A method for preparing a bio-based water-based pressure-sensitive adhesive with a high biocarbon content comprises the following steps; (a) Preparation of monomer pre-emulsion: Deionized water and emulsifier were weighed and added into an emulsifying kettle with high-speed stirring. Soft monomer, hard monomer and functional monomer were slowly added successively and stirred evenly at a speed of 600 rpm to obtain monomer pre-emulsion.

[0035] (b) Weigh deionized water and emulsifier, add them into a reaction kettle, stir and heat to 70-85°C, take 3-6wt% of the total monomer pre-emulsion liquid and add it into the reaction kettle, add part of the initiator, and polymerize for 25-35 minutes.

[0036] (c) Slowly add the remaining monomer pre-emulsion and initiator solution dropwise into the reactor over 3-4 hours.

[0037] (d) After the reaction is completed, the mixture is kept warm for 30-90 minutes, and after adjusting the pH value and viscosity, it can be coated and dried to form a water-based pressure-sensitive adhesive.

[0038] Except for special statements, the equipment used in each embodiment and comparative example can be obtained from commercial sources. Among them: In the following embodiments and test examples, the experimental equipment required is as follows: Rolling ball method initial adhesion tester (HP-CZY-G): Jinan Hengpin Electromechanical Technology Co., Ltd.; Normal temperature tape adhesion tester (HP-CZY-6S): Jinan Hengpin Electromechanical Technology Co., Ltd.; NKT6100-B laser particle size analyzer: Shandong Naikete Analytical Instrument Co., Ltd.; Universal tensile testing machine; Laboratory coating machine. The raw materials or reagents not specifically described in the present invention are all conventional raw materials in the field and can be purchased through commercial channels.

[0039] Alkylphenol polyoxyethylene ether-10 (OP-10), supplier: Aladdin, product number: O304931.

[0040] Example 1 Preparation of Bio-based Water-based Pressure-Sensitive Adhesive Latex The following steps are involved: Add 39.95 g of deionized water, 3.81 g of alkylphenol polyoxyethylene ether-10 (OP-10) (supplier: Aladdin, item number: O304931), 1.91 g of sodium dodecyl sulfate to the pre-emulsification kettle, heat to 50°C, start mechanical stirring at a stirring rate of 600 rpm, and then add 45.74 g of n-butyl acrylate, 75.92 g of dibutyl fumarate, 2.55 g of acrylic acid, and 0.25 g of sodium bicarbonate in sequence at a rate of 6 ml / min. After the pre-emulsification lasts for 60 min, take out the monomer pre-emulsion liquid for use.

[0041] Add 42.75 g of deionized water, 0.95 g of alkylphenol polyoxyethylene ether-10, and 0.475 g of sodium dodecyl sulfate to the reactor, heat to 70°C, set the stirring rate to 250 rpm, then dissolve 1.01 g of potassium persulfate initiator in 20.37 g of deionized water and add it to the reactor at a rate of 1.1 ml / min. Then add 8.48 g of monomer pre-emulsion at one time, react for 30 min, and take out to obtain seed emulsion for use.

[0042] The seed emulsion should be obviously bluish white in a dark place.

[0043] The reserved seed emulsion was taken out and added to the reactor, the temperature was raised to 70°C, the stirring rate was set to 250 rpm, 0.61 g of potassium persulfate initiator was dissolved in 13.15 g of deionized water, and the remaining monomer pre-emulsion (at a rate of 1.1 ml / min) and potassium persulfate aqueous solution (at a rate of 0.08 ml / min) were slowly added to the reactor within 4 h using a peristaltic pump.

[0044] During the reaction, the emulsion gradually changed from bluish white to milky white.

[0045] The final emulsion after the reaction is completed is taken out, and the particle size distribution of the latex particles in the final emulsion is characterized using a laser particle size meter. The results are as follows: Figure 3 shown.

[0046] The pH value of the emulsion after the reaction was adjusted to 7 with ammonia water, and the gel-like residue was removed by filtering with wire mesh to obtain an aqueous pressure-sensitive adhesive emulsion. 0.6 g of trimethylolpropane-tri[3-(2-methylaziridinyl) propionate] was added to the emulsion as a crosslinking agent, and the aqueous pressure-sensitive adhesive emulsion was evenly coated on the surface of the corona-treated release film (S75TA3, release force 5-8gf / ml, 75 um, Shenzhen Shunhexing Electronic Materials Co., Ltd.) with a coating rod. The process parameters of the corona treatment were: plasma treatment time of 180 seconds, treatment distance of 5 cm, and plasma treatment voltage of 30 volts.

[0047] The water-based pressure-sensitive adhesive emulsion has a milky white appearance with a bluish tint, is fine and smooth, has no obvious granular gel residue, and has a small residual monomer odor.

[0048] Take about 2 g of the final emulsion and place it in an aluminum pan, then place the aluminum pan in a 120°C forced air oven, take it out and weigh it every 30 minutes until the weight remains constant. The solid content is the ratio of the remaining mass of the emulsion after drying to the mass of the emulsion sample.

[0049] The final emulsion solid content of Example 1 is about 50%.

[0050] The release film coated with the emulsion was placed in a 60°C forced air oven for 30 minutes to cure into a film. The release film was then used to cover the adhesive layer to produce a water-based pressure-sensitive adhesive tape, with an adhesive layer thickness of about 200 um.

[0051] Example 2 Preparation of bio-based water-based pressure-sensitive adhesive latex The following steps are involved: Add 25.10 g of deionized water, 2.25 g of OP-10, and 1.13 g of sodium dodecyl sulfate to the pre-emulsification kettle, heat to 50°C, start mechanical stirring at a stirring rate of 600 rpm, and then add 30.00 g of n-butyl acrylate, 45.90 g of dibutyl fumarate, 1.5 g of acrylic acid, and 0.15 g of sodium bicarbonate in sequence at a rate of 6 ml / min. After pre-emulsification for 60 min, take out the monomer pre-emulsion liquid for use.

[0052] Add 25.02 g of deionized water, 0.56 g of OP-10, and 0.28 g of sodium dodecyl sulfate to the reactor, heat to 70°C, set the stirring rate to 250 rpm, and then dissolve 0.70 g of potassium persulfate initiator in 13.00 g of deionized water and add it to the reactor at a rate of 1.1 ml / min. Then add 3.00 g of monomer pre-emulsion at one time, react for 30 min, and take out to obtain seed emulsion for use.

[0053] The seed emulsion should be obviously bluish white in a dark place.

[0054] The reserved seed emulsion was taken out and added to the reactor, the temperature was raised to 70°C, the stirring rate was set to 250 rpm, 0.35 g of potassium persulfate initiator was dissolved in 7.5 g of deionized water, and the remaining monomer pre-emulsion (at a rate of 1.1 ml / min) and potassium persulfate aqueous solution (at a rate of 0.08 ml / min) were slowly added to the reactor within 4 h using a peristaltic pump.

[0055] During the reaction, the emulsion gradually changed from bluish white to milky white.

[0056] The final emulsion after the reaction was taken out, and the particle size distribution of the latex particles of the final emulsion was characterized using the NKT6100-B laser particle size meter of Shandong NIKET Analytical Instrument Co., Ltd. The results are as follows: Figure 3 shown.

[0057] The pH value of the emulsion after the reaction was adjusted to 7 with ammonia water, and the gel-like residue was removed by filtering with wire mesh to obtain an aqueous pressure-sensitive adhesive emulsion. 0.38 g of trimethylolpropane-tris[3-(2-methylaziridinyl) propionate] was added to the emulsion as a crosslinking agent, and the aqueous pressure-sensitive adhesive emulsion was evenly coated on the surface of a release film (S75TA3, release force 5-8 gf / ml, 75 um, Shenzhen Shunhexing Electronic Materials Co., Ltd.) treated with corona (process parameters of corona treatment: plasma treatment time of 180 seconds, treatment distance of 5 cm, corona treatment voltage of 30 volts) using a coating rod.

[0058] The water-based pressure-sensitive adhesive emulsion has a milky white appearance with a bluish tint, is fine and smooth, has no obvious granular gel residue, and has a small residual monomer odor.

[0059] Take about 2 g of the final emulsion and place it in an aluminum pan, then place the aluminum pan in a 120°C forced air oven, take it out and weigh it every 30 minutes until the weight remains constant. The solid content is the ratio of the remaining mass of the emulsion after drying to the mass of the emulsion sample.

[0060] The final emulsion solid content of Example 2 is about 56%.

[0061] The release film coated with the emulsion was placed in a 60°C forced air oven for 30 minutes to cure into a film. The release film was then used to cover the adhesive layer to produce a water-based pressure-sensitive adhesive tape, with an adhesive layer thickness of about 200 um.

[0062] Example 3 Preparation of bio-based water-based pressure-sensitive adhesive latex The following steps are involved: Add 30.95 g of deionized water, 3.81 g of OP-10, and 1.91 g of sodium dodecyl sulfate to the pre-emulsification kettle, heat to 50°C, start mechanical stirring at 600 rpm, and then add 30.74 g of n-butyl acrylate, 50.92 g of dibutyl fumarate, 2.55 g of acrylic acid, and 0.25 g of sodium bicarbonate in sequence at a rate of 6 ml / min. After pre-emulsification for 60 min, take out the monomer pre-emulsion for use.

[0063] Add 23.75 g of deionized water, 0.95 g of OP-10, and 0.475 g of sodium dodecyl sulfate to the reactor, heat to 70°C, set the stirring rate to 250 rpm, and then dissolve 1.01 g of potassium persulfate initiator in 20.37 g of deionized water and add it to the reactor at a rate of 1.1 ml / min. Then add 8.48 g of monomer pre-emulsion at one time, react for 30 min, and take out to obtain seed emulsion for use.

[0064] The seed emulsion should be obviously bluish white in a dark place.

[0065] The reserved seed emulsion was taken out and added to the reactor, the temperature was raised to 70°C, the stirring rate was set to 250 rpm, 0.61 g of potassium persulfate initiator was dissolved in 13.15 g of deionized water, and the remaining monomer pre-emulsion (at a rate of 1.1 ml / min) and potassium persulfate aqueous solution (at a rate of 0.08 ml / min) were slowly added to the reactor within 4 h using a peristaltic pump.

[0066] During the reaction, the emulsion gradually changed from bluish white to milky white.

[0067] The final emulsion after the reaction is completed is taken out, and the particle size distribution of the latex particles in the final emulsion is characterized using a laser particle size meter. The results are as follows: Figure 3 shown.

[0068] The pH value of the emulsion after the reaction was adjusted to 7 with ammonia water, and the gelatinous residue was removed by filtering with a wire mesh to obtain an aqueous pressure-sensitive adhesive emulsion. 0.41 g of trimethylolpropane-tris[3-(2-methylaziridinyl)propionate] was added to the emulsion as a crosslinking agent, and the aqueous pressure-sensitive adhesive emulsion was evenly coated on the surface of the release film treated with corona using a coating rod.

[0069] The water-based pressure-sensitive adhesive emulsion has a milky white appearance with a bluish tint, is fine and smooth, has no obvious granular gel residue, and has a small residual monomer odor.

[0070] Take about 2 g of the final emulsion and place it in an aluminum pan, then place the aluminum pan in a 120°C forced air oven, take it out and weigh it every 30 minutes until the weight remains constant. The solid content is the ratio of the remaining mass of the emulsion after drying to the mass of the emulsion sample.

[0071] The final emulsion solid content of Example 3 is about 55%.

[0072] The release film coated with the emulsion was placed in a 60°C forced air oven for 30 minutes to cure into a film. The release film was then used to cover the adhesive layer to produce a water-based pressure-sensitive adhesive tape, with an adhesive layer thickness of about 200 um.

[0073] Comparative Example 1 Preparation of bio-based water-based pressure-sensitive adhesive latex.

[0074] The following steps are involved: Add 30.55 g of deionized water, 2.90 g of alkylphenol polyoxyethylene ether-10, 1.00 g of sodium dodecyl sulfate to the pre-emulsification kettle, heat to 50°C, start mechanical stirring at 600 rpm, and then add 44.20 g of n-butyl acrylate, 44.22 g of dibutyl fumarate, 1.79 g of acrylic acid, and 0.18 g of sodium bicarbonate in sequence at a rate of 6 ml / min. After pre-emulsification for 60 min, take out the monomer pre-emulsion for use.

[0075] Add 30.51 g of deionized water, 0.79 g of OP-10, and 0.25 g of sodium dodecyl sulfate to the reactor, heat to 70°C, set the stirring rate to 250 rpm, and then dissolve 1.04 g of potassium persulfate initiator in 20.99 g of deionized water and add it to the reactor at a rate of 1.1 ml / min. Then add 8.34 g of monomer pre-emulsion at one time, react for 20 min, and take out the seed emulsion for use.

[0076] The seed emulsion should be obviously bluish white in a dark place.

[0077] Take out the reserved seed emulsion and add it into the reactor, raise the temperature to 70°C, set the stirring rate to 250 rpm, dissolve 0.45 g of potassium persulfate initiator in 10.03 g of deionized water, and use a peristaltic pump or a separatory funnel to slowly add the remaining monomer pre-emulsion (at a rate of 0.7-1.1 ml / min) and potassium persulfate aqueous solution (at a rate of 0.05-0.08 ml / min) into the reactor within 4 h.

[0078] During the reaction, the emulsion gradually changed from bluish white to milky white.

[0079] The final emulsion after the reaction is completed is taken out, and the particle size distribution of the latex particles in the final emulsion is characterized using a laser particle size meter. The results are as follows: Figure 3 shown.

[0080] The pH value of the emulsion after the reaction is adjusted to 7 with ammonia water, and the gel-like residue is removed by filtering with a wire mesh to obtain an aqueous pressure-sensitive adhesive emulsion. 0.38 g of trimethylolpropane-tris[3-(2-methylaziridinyl) propionate] is added to the emulsion as a crosslinking agent, and the aqueous pressure-sensitive adhesive emulsion is evenly coated on the mirror stainless steel substrate or the surface of the release film treated with corona using a coating rod.

[0081] The water-based pressure-sensitive adhesive emulsion has a milky white appearance with a bluish tint, is fine and smooth, has no obvious granular gel residue, and has a small residual monomer odor.

[0082] Take about 2 g of the final emulsion and place it in an aluminum pan, then place the aluminum pan in a 120°C forced air oven, take it out and weigh it every 30 minutes until the weight remains constant. The solid content is the ratio of the remaining mass of the emulsion after drying to the mass of the emulsion sample.

[0083] The final emulsion solid content in the comparative example 1 is about 50%.

[0084] The release film coated with the emulsion was placed in a 60°C forced air oven for 30 minutes to cure into a film. The release film was then used to cover the adhesive layer to produce a water-based pressure-sensitive adhesive tape, with an adhesive layer thickness of about 200 um.

[0085] The initial tack of the tape was tested according to the test method for initial tack of pressure-sensitive adhesive tapes (GB / T4852-2002). The initial tack was determined by the size of the ball. The larger the ball, the stronger the initial tack. The lasting tack of the tape was tested according to the test method for lasting tack of the tapes (GB / T 4851-2014). The lasting tack was determined by the debonding time. The longer the time, the stronger the lasting tack.

[0086] Table 1 Service performance test results of the embodiment

[0087] Figure 1 :Synthetic route for bio-based water-based pressure-sensitive adhesive using fumaric acid.

[0088] Figure 2 : Infrared spectrogram of the emulsion demulsification precipitation in Example 1, at 1750cm -1 The C=O stretching vibration characteristic peaks are the ester groups on the side chains of n-butyl acrylate and dibutyl fumarate, and there is no peak at 1645 cm -1 A strong C=C stretching vibration characteristic peak appears at 3000 cm -1 There is a strong OH stretching vibration characteristic peak, indicating the presence of hydrogen bonds in the sample. The above results show that the chemical composition of the water-based pressure-sensitive adhesive synthesized in Example 1 is in line with expectations.

[0089] Figure 3 : The latex particle diameter distribution diagram of Examples 1-3 and Comparative Example 1, the latex particle size will affect its subsequent curing process and final performance, but it is difficult to control the latex particle size in practice. In the examples and comparative examples, the latex particle size is controlled as much as possible to maintain a single peak and the distribution is relatively close.

Claims

1. A method for preparing a bio-based water-based pressure-sensitive adhesive with a high biocarbon content, characterized in that: The high biochar content bio-based water-based pressure-sensitive adhesive is made of raw materials including the following components, wherein the raw materials are as follows by weight: 280-380 parts of deionized water, 1-3 parts of sodium bicarbonate, 25-35 parts of emulsifier, 180-280 parts of soft monomer S1, 200-300 parts of hard monomer S2, 5-12 parts of functional monomer, 5-12 parts of persulfate initiator and 5-12 parts of aziridine crosslinking agent; the emulsifier is an alkyl sulfate anionic surfactant A and a polyoxyethylene ether nonionic surfactant B; The soft monomer S1 is at least one of n-butyl acrylate and 2-ethylhexyl acrylate; The hard monomer S2 is dibutyl fumarate; The functional monomer is at least one of acrylic acid and 4-hydroxybutyl acrylate; The aziridine cross-linking agent is trimethylolpropane-tris[3-(2-methylaziridinyl) propionate].

2. The method according to claim 1, characterized in that The alkyl sulfate anionic surfactant A is sodium dodecyl sulfate; the polyoxyethylene ether nonionic surfactant B is OP-10; and the persulfate initiator is potassium persulfate.

3. The method according to claim 1, characterized in that The method comprises the following steps: (a) preparing monomer pre-emulsion: weighing deionized water and emulsifier, adding them into an emulsifying kettle and stirring, successively adding soft monomer, hard monomer, functional monomer and sodium bicarbonate, stirring evenly to prepare monomer pre-emulsion; Preferably, in the monomer pre-emulsion, the mass fraction ratio of the soft monomer to the hard monomer is in the range of 1:1-1.7; Preferably, in the monomer pre-emulsion, the mass proportion of the functional monomer is in the range of 2-4 wt % of the total mass of the three monomers; Preferably, in the monomer pre-emulsion, the mass proportion of deionized water is 20-40 wt %, more preferably 23-27 wt %; (b) weighing deionized water and an emulsifier, adding them into a reaction kettle, stirring and heating to 70-85° C., adding 3-6 wt % of the total amount of the monomer pre-emulsion prepared in step (a) into the reaction kettle, adding part of the initiator and deionized water, and polymerizing for 25-35 minutes; Preferably, the mass ratio of deionized water and emulsifier added to the reactor is in the range of 28-45:1; Preferably, the initiator added to the reactor is 30% to 70% of the total mass of the initiator; Preferably, the mass ratio of initiator to emulsifier is 0.2-0.8:1; (c) adding the remaining monomer pre-emulsion, the remaining initiator and deionized water dropwise into the reaction kettle within 3-4 hours; (d) After the reaction is completed, the pH value and viscosity are adjusted, and then an aziridine crosslinking agent is added to the emulsion, which is then coated and dried to form a water-based pressure-sensitive adhesive.

4. The method according to claim 3, characterized in that In step (a), the mass proportion of deionized water in the monomer pre-emulsion is 22-35 wt %, more preferably 23-27 wt %; Preferably, during the monomer pre-emulsification process, the stirring speed is preferably 200-1000 rpm, more preferably 500-1000 rpm.

5. The method according to claim 3, characterized in that: In step (a), the monomers in the monomer pre-emulsion are added in the order of their polarity from weak to strong.

6. The method according to claim 3, characterized in that: In step (a), the total amount of the two emulsifiers in the monomer pre-emulsion is preferably 2.5-5 wt % of the monomer, more preferably 4.5-4.8 wt %; During the monomer pre-emulsification process, the preferred emulsification temperature is 25-50°C, more preferably 35-50°C; During the monomer pre-emulsification process, the preferred emulsification time is 30 min-120 min, more preferably 60-90 min.

7. The method according to claim 3, characterized in that In step (b), the deionized water added to the reactor is preferably 25-40 wt % of the monomer, more preferably 30-35 wt %; The total amount of the two emulsifiers added to the reactor is preferably 1-1.5 wt % of the monomers, more preferably 1.1-1.3 wt %.

8. The method according to claim 3, characterized in that In step (b), the ratio of the two emulsifiers is preferably anionic surfactant: nonionic surfactant 1:3, more preferably anionic surfactant: nonionic surfactant 1:2; In the step (b), the mass fraction of the monomer pre-emulsion added first is preferably 3-10 wt %, more preferably 3-5 wt %; In the step (b), the temperature required for the reaction depends on the type of thermal initiator; In the step (b), the particle size of the obtained polymer emulsion is preferably 50-200 nanometers, more preferably 50-100 nanometers; In the step (b), the added initiator is preferably 30-45 wt% of the total initiator amount, more preferably 30-35 wt% of the total initiator amount.

9. A bio-based water-based pressure-sensitive adhesive with high biocarbon content prepared by the method according to any one of claims 1 to 8.

10. The use of the pressure-sensitive adhesive according to claim 9, characterized in that: The pressure-sensitive adhesive emulsion is made into a pressure-sensitive adhesive tape, and the pressure-sensitive adhesive emulsion needs to go through the following steps to make a pressure-sensitive adhesive tape: (1) Use ammonia water to adjust the pH value to 7 before leaving the kettle; (2) removing the scum by suction filtration to obtain an aqueous pressure-sensitive adhesive latex; (3) Add 0.4-0.8 wt% of the cross-linking agent based on the weight of the monomer and stir thoroughly; (4) coating the aqueous pressure-sensitive adhesive latex on a release film or substrate, drying excess water in a blast oven, and protecting and covering with a release film.

Citation Information

Patent Citations

  • Bio-based pressure-sensitive adhesive and preparation method thereof

    CN114958300A

  • Acrylic emulsion pressure sensitive adhesive and preparation method thereof

    CN107722882A

  • Removable emulsion acrylate pressure sensitive adhesive containing organosilicon cross-linking agent and preparation method thereof

    CN109575852A

  • High-performance protective film emulsion pressure-sensitive adhesive liquid, preparation method thereof, pressure-sensitive adhesive and protective film

    CN116589953A

  • Acrylate emulsion pressure-sensitive adhesive for masking paper masking tape and preparation method of acrylate emulsion pressure-sensitive adhesive

    CN118562425A